●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Hi my lil bunny!
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
Let's solve your equation step-by-step.
[tex]3(x+7)-14=22[/tex]
Step 1: Simplify both sides of the equation.
[tex]3 ( x + 7 ) - 14 = 22\\(3)^(x) + (3) (7) + - 14 = 22[/tex] (Distribute)
[tex]3x + 21 + -14 = 22[/tex]
[tex]( 3x) + (21 + -14 ) = 22[/tex] (Combine Like Terms)
[tex]3x + 7 = 22\\3x + 7 = 22[/tex]
Step 2: Subtract 7 from both sides.
[tex]3x + 7 - 7 = 22 - 7 \\3x = 15[/tex]
Step 3: Divide both sides by 3.
[tex]\frac{3x}{3} = \frac{15}{3} \\x = 5[/tex]
So your answer would be : [tex]\boxed {x = 5}[/tex]
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Have a great day/night!
❀*May*❀